Comparative Analysis of Liberty Market and DHA Y-Block Market Based on Urban Marketplace Vitality Parameters - Batool, Maham; Rehman, Nida; Jalil, Adnan (Journal of Art, Architecture and Built Environment, 2024)
Vitality is the quality that keeps any public space lively and functional throughout the day. A vibrant and dynamic marketplace is considered as the heart and soul of a city. Lahore, being a provincial capital, hosts many commercial hubs that have evolved over different periods of time and play a significant role in the city’s overall urban setting. This research investigates the factors contributing to the vitality of an urban marketplace. For this purpose, Liberty Market and DHA Y-Block Market are compared. Liberty Market, located in the central area of Gulberg, has been an expanding shopping facility ever since its establishment in 1967. Its strategic location and connectivity makes it easily accessible from all parts of the city. In contrast, DHA Y-Block Market, established in 1995, serves only the residents of DHA and nearby societies. A comparative analysis of these two markets was conducted using established vitality parameters derived from comprehensive literature sources. Mixed-methods approach was employed including frequent site visits, photographic surveys, interviews with the stakeholders, and questionnaire surveys to capture user experience and opinion. Secondary data was gathered through a comprehensive literature review deduced from historical writings and digital libraries. An analytical framework was developed to thoroughly review and critically analyze the collected data. The comparative analysis revealed the strengths and weaknesses of these commercial hubs in view of vitality parameters. Based on the identified issues, specific design interventions were proposed to enhance the overall vitality of these markets.